Caracterização hidrogeomorfológica da bacia hidrográfica do Rio Branco, estado de Roraima, Brasil. - Carvalho, Thiago Morato de (2018)
The thematic of this thesis is about on the structure and functioning of the hydrodynamics in the wetlands of Roraima, in particular, it focuses on how the physiographic characteristics and periodic flood patterns behave in the different environments of the Branco drainage basin. There are several questions that may lead to a better understanding of the environments that form the Branco drainage basin, this research aims at answering some questions like: a) How the Branco drainage basin is inserted in the State of Roraima, taking into account its geomorphological aspects associated in denudational and agradational environments? b) How does the hydrogeomorphological dynamics of the Branco river occur and its relation with the biogeographic aspects, in this case, is possible if the vegetation can provide subsidies for a classification? c) How are the wetlands of the Branco drainage basin characterized, and how can they contribute to a better understanding of the dynamics of this fluvial system? This thesis is structured in a format that presents the results formatted in the form of scientific articles, with the classic divisions containing introduction, methodology, results and discussion pertinent to the theme of this thesis. With regard to the themes of the articles, these cover the following themes: classification of the denudational and agradational environments of Roraima; hydrological and dynamic aspects of the Branco river; characteristics and classification of non-fluvial lacustrine systems in the Northeast of Roraima; morphometry of the upper Branco river; and floristic of Branco river as support to the classification being a typical environment of várzea or igapó. These results are presented in appendices 1 through 5. From the perspective of the studies presented here, they have information that, together with others, will contribute to understanding we have about the environments that are periodically flooded in this part of the Amazon. This contribution can be focused on the academic aspect, in order to acquire a new knowledge and under the aspect of the application of generated knowledge, being important to overcome problems of territorial and environmental management, serving as a methodological basis for characterization of physiographic aspects of the landscape and the understanding of its spatio-temporal dynamics.